Evaluation of D-Dimer in the diagnosis of suspected deep vein thrombosis - Mahmmod, Khalid A. (AL-Kindy College Medical Journal, 2014)
Background: Deep vein thrombosis is a multi causal disease and its one of most common venous disorder, but only one quarter of the patients who have signs and symptoms of a clot in the vein actually have thrombosis and need treatment .The disease can be difficult to diagnose. Venous ultrasound in combination with clinical finding is accurate for venous thromboembolism, its costly because a large number of patients with suspicious signs and symptoms. Venography still the gold standard for venous thromboembolism but it is invasive. The D-dimer increasingly is being seen as valuable tool rolling out venous thromboembolism and sparing low risk patients for further workup.Objectives: this study has designed the role of D-dimer to confirm diagnosis of deep vein thrombosis for patients with positive Doppler and those show no features of thrombosis in Doppler using more accurate and sensitive instrument measuring the concentration of D- dimer.Methods: Thirty patients with deep vein thrombosis diagnosed by Doppler and clinical signs and symptoms (for those with negative Doppler) assessed for D- dimer by automachine cormy accent 200 based on immunoassay which more sensitive than the ordinary methods.Results: Twenty-eight patients out of thirty shows a significant elevation of D-dimer compared to control group which show no elevation in D- dimer level. On other side higher level of D- dimer found in those with negative Doppler as same as level to the patients with positive Doppler.Conclusion: Patients with clinical sign and symptoms of deep vein thrombosis and negative Doppler should be assessed for D- dimer using more sensitive technique based on immunological assay.Key words: deep vein thrombosis (DVT) pulmonary embolism (PE), Doppler